Potential of morphology-based Pterydophyta diversity in supporting field-based practicum of low plant botany learning - Y. Yudhistian; Tabitha Sri Hartati Wulandari (JPBI (Jurnal Pendidikan Biologi Indonesia), 2024)
Field-Based Practicum (FBP) about Pterydophyta diversity material in Low plant botany learning is very important, even though the facts in the field show that FBP is still minimally carried out. This research aims to utilize the potential diversity of Pterydophyta in the Tuban-Lamongan Pantura area as a support for FBP about low plant botany learning. The type of research is descriptive exploratory with a transect method, which divides the research area into five plots. Data collection techniques involve observing abiotic parameters and fern morphology in each plot and counting the number of individuals of each species. Data analysis used the Shannon & Wiener index for diversity and qualitative descriptive analysis for morphology. The research results showed 19 species of ferns with 210 individuals divided into two classes, namely Polypodiopsida and Psyotopsida. The fern diversity index is in the medium category (H´=2.10). The diversity of ferns obtained shows that the Tuban-Lamongan Pantura area has a high potential to support FBP about low plant botany learning to provide insight and direct experience to students about the diversity of ferns in the surrounding environment.